The Influence of Leadership Type, Motivation, Work Discipline and Human Resource Quality on the Performance of KPU-D Employees in Cimahi City, West Java Province - Adi Nugroho, Febrianto (Syntax Corporation Indonesia, 2024)
After the New Order, Indonesia's electoral system underwent various changes to achieve governability, which is effective governance. So the performance of KPU employees plays an important role in ensuring the implementation of elections that are smooth and free from technical dynamics. However, in the 2019 General Election, the performance of the Cimahi City KPUD Secretariat faced a number of problems, such as ineffective coordination, information delays, inadequate complaint handling, resource shortages, administrative errors, and lack of technical assistance. This affected the smooth running and public trust in the electoral process. This study aims to analyze the influence of leadership style, motivation, work discipline, and the quality of human resources on the performance of Cimahi City KPUD employees, both partially and together. The study used an explanatory quantitative approach with regression analysis method. The research sample consisted of 195 respondents selected using proportionate stratified random sampling. Data collection was done through documentation, Likert scale-based questionnaires, and literature study. Data analysis includes validity, reliability, simple and multiple linear regression tests, as well as F and T tests. The results showed a positive and significant influence of leadership style variables (65.1%), work motivation (65.1%), work discipline (58.4%), and quality of human resources (76.4%) on employee performance. Together, the four variables have an influence of 83.9% on the performance of Cimahi City KPUD employees. This study emphasizes the importance of improving the quality of leadership, motivation, work discipline, and human resources to support the implementation of better elections.